Gênero, sexualidade e currículo: percepções e proposições a partir de vivências em uma escola médica - Oliveira, Pedro Mendonça de (Universidade Federal de São Carlos, 2020)
Michel Foucault characterizes sexuality as a device of power, which has been utilized throughout the history of mankind for the maintenance of privileges. Since the nineteenth century, this device finds in medical practice one of its principal mechanisms. Medical education tends to endorse heteronormative discourse and diagnose deviant behavior as pathologies. Concerning gender, it promotes a binary portrayal of individuals, most often assuming heterosexuality. The medical school at the Federal University of São Carlos (UFSCar) uses the constructivist spiral as an educational methodology, which, like other active methodologies, guarantees student protagonism and stimulates interchange with their previous world knowledge. This methodology relies on the concept of Meaningful Learning. The aim of this study was to understand, following the students' perspective, how a competency profile related to gender and sexuality is developed at the medical school at UFSCar. The data was gathered through focus groups, and was analyzed with the use of the meaning interpretation method. The results show that there is a positive, though indirect, influence from the use of Active Methodologies, especially if we contrast them with more traditional methodologies. There is also evidence of a lack of preparation by professors of the area in regard to gender/sexuality issues. In additional discussion, we address the Curriculum and Extra-curricular activities that influence the acquisition of competencies by improving or hindering it. In this regard, we propose a new concept: the "Marginal Curriculum". In conclusion, we recognize that active methodologies of education figure as a counter-hegemonic strategy in face of the maintenance of biopower through sexuality, and propose new applicable ways in the reorientation of the curriculum´s contents.
Gender, sexuality and curriculum: perceptions and propositions from experiences in a medical school
Keywords: Educação médica; Currículo; Aprendizagem baseada em problema; Identidade de gênero; Sexualidade; Education medical; Curriculum; Problem-based learning; Gender identity; Sexuality; CIENCIAS DA SAUDE::SAUDE COLETIVA